HELPPPPPPPPP 55 POINTS Isabel graphed the following system of equations.

2x – y = 6

y = -3x + 4



She came up with the solution (2,-2).

What were the 3 steps she did to get that solution?(Make sure they are in the correct order)

1)_______________________
2)_______________________
3)_______________________

HELPPPPPPPPP 55 POINTS Isabel graphed the following system of equations 2x y 6 y 3x 4 She came up with the solution 22 What were the 3 steps she did to get that class=

Respuesta :

Answer:

1.  Substitute y = -3x +4 for y in the first equation

2.  Combine like terms and isolate x

3.  Substitute in x into the 2nd equation to get y

Step-by-step explanation:

1.  Substitute y = -3x +4 for y in the first equation

2x- (-3x+4) = 6

2.  Combine like terms

5x -4 = 6

5x -4 +4 = 6+4

5x=10  Divide by 5 to isolate x

5x/5 =10/5

x=2

3. Substitute in x into the 2nd equation to get y

y = -3x +4

y = -3(2) +4

y = -6+4

y=-2

(2,-2)